Răspunsuri

2014-11-05T22:30:35+02:00
a)x-6=(2-x)+1/3
x+x=2+6+1/3
2x=8+1/3
2x=(8
·3+1)/3
2x/1=25/3
2x·3=25
x=25/6=4,1(6)
b)2(x-3)+=x+
2x-6+11/4=x+3/2
2x-x=6-11/4+3/2
x=(6
·4-11+3·2)/4
x=19/4
c)(x-4)+x=(x+2)-3
x-4+x=x/3+2/3-3
2x-x/3=4+2/3-3
(2x
·3-x)/3=1+2/3
(6x-x)/3=(3+2)/3
5x=5
x=5/5
x=1
d)(x+2)+=(x-3)+2
3x/8+6/8+?
e)0,(6)·(x+3)-0,(3)·(2x+1)=0,(5)·(x+2)
0,(6)=6/9=2/3
0,(3)=3/9=1/3
0,(5)=5/9
2/3(x+3)-1/3(2x+1)=5/9(x+2)
2x/3+6/3-2x/3-1/3=5x/9+10/9
2-1/3=5x/9+10/9
-5x/9=-2+1/3+10/9
-5x/9=(-2
·9+3+10)/9
-5x/9=(-18+3+10)/9
-5x/9=(-15+10)/9
-5x/9=-5/9     (-1)
5x=5
x=5/5
x=1